Collaborative Music Learning : Utilizing n-Track Application in Private Music Education - Piter Sembiring; Yudi Sukmayadi; Ayo Sunaryo (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2025)
This study explores the utilization of n-Track, a digital audio workstation (DAW), as a collaborative tool in private music education. Unlike conventional music learning tools, n-Track enables real-time digital collaboration between teachers and students, facilitating asynchronous learning. This study presented a novel approach by utilizing mobile based DAW technology to enhance both in person and virtual music instruction, making it more accessible and interactive. Using a qualitative approach with a descriptive method, data was collected through observations and interviews with students engaged in n-Track-based learning. Thematic coding was used to identify recurring patterns and themes in the data, providing insights into the app’s impact on student and teacher interaction. The findings indicate that n-Track enhances student engagement, supports independent practice, and improves teacher-student interaction efficiency. Key features such as multitrack recording, MIDI sequencing, and real-time feedback facilitate structured musical arrangements and instrumental skill development. This study also highlights the importance of digital literacy among educators to maximize the benefits of technology in music education. Despite limitations in the free version of n-Track, it remains effective in fostering creativity and autonomy in music learning. This research contributes to the advancement of digital music pedagogy, emphasizing the role of DAWs in modern music education.